Smart mobile advertiser (SMA) - Mohd Shahrul Khairy, Awang Kenal (2010)
Nowadays,mobile phones are widely use in our daily life and most of us cannot avoid from using this new technology.When the mobile phone is connected with the internet,it will be a very powerful device where user can receive or send any data from the internet anywhere and any place.Because of this factor,Smart Mobile Advertiser (SMA) is developed.SMA is an application that can involve in mobile user advertising activities and make it more interesting.SMA can help user to register as a community and store all their advertising records.The system Development Life Cycle (SDLC) methodology has been chosen for development of this.This system is using a distributed system concept which involves three items such as web services,server (SQL SERVER 2005) and PDA or hand phone that have a window mobile 5.SMA brought together the technologies from Microsoft.NET 2003 which is the MS.NET Compact Framework in particular, Microsoft SQL Server 2000 as the central database and XML as a persistent database in the hardware (PDA).